Wind temperature prediction model for ventilation cooling in excavation roadway containing cemented tailings backfill heat sources - Dingyi Wei; Weijie Cao; Cuifeng Du; Zhun Li; Fan Zhang; Junjie Guo (Case Studies in Thermal Engineering)
The application of backfill mining method in deep mines is becoming more and more common, but the accompanied hydration heat of cemented tailings backfill (CTB) exacerbates the thermal damage in the depths. This study establishes and validates the wind temperature prediction model of excavation roadway containing CTB heat sources according to the simulation results and field measurements. The results show that the hydration heat of CTB has an important influence on the wind temperature in excavation roadway, and the use of ventilation to alleviate it is effective. The wind temperature increases gradually with the distance between the measurement point and air duct. The overall mean absolute percentage error (MAPE) between the theoretical calculated values and the simulated values of the established wind temperature prediction model of excavation roadway containing CTB is 0.08 %, which verifies the accuracy and validity of the model. The wind temperature prediction model can be used to guide the development of appropriate ventilation and cooling programs at the site, providing a guarantee for personnel health and safe and efficient mine production.